Long‐term results of a three arms prospective cohort study on implants in periodontally compromised patients: 10‐year data around sandblasted and acid‐etched (SLA) surface. Issue 10 (19th July 2013) - Roccuzzo, Mario; Bonino, Luca; Dalmasso, Paola; Aglietta, Marco
Abstract Objectives The aim of this study was to compare the long‐term outcomes of sandblasted and acid‐etched (SLA) implants in patients previously treated for periodontitis and in periodontally healthy patients (PHP). Material and methods One hundred and forty‐nine partially edentulous patients were consecutively enrolled in private specialist practice and divided into three groups according to their periodontal condition: PHP, moderately periodontally compromised patients (PCP) and severely PCP. Implants were placed to support fixed prostheses, after successful completion of initial periodontal therapy. At the end of active periodontal treatment (APT), patients were asked to follow an individualized supportive periodontal therapy (SPT) program. Diagnosis and treatment of peri‐implant biological complications were performed according to cumulative interceptive supportive therapy (CIST). At 10 years, clinical and radiographic measures were recorded by two calibrated operators, blind to the initial patient classification, on 123 patients, as 26 were lost to follow up. The number of sites treated according to therapy modalities C and D (antibiotics and/or surgery) during the 10 years was registered. Results Six implants were removed for biological complications. The implant survival rate was 100% for PHP, 96.9% for moderate PCP and 97.1% for severe PCP. Antibiotic and/or surgical therapy was performed in 18.8% of cases in PHP, in 52.2% of cases in moderate PCP and in 66.7% cases in severe PCP, with a statistically significant differences between PHP and both PCP groups. At 10 years, the percentage of implants, with at least one site that presented a PD ≥ 6 mm, was, respectively, 0% for PHP, 9.4% for moderate PCP and 10.8% for severe PCP, with a statistically significant difference between PHP and both PCP groups. Conclusions This study shows that SLA implants, placed under a strict periodontal control, offer predictable long‐term results. Nevertheless, patients with a history of periodontitis, who did not fully adhere to the SPT, presented a statistically significant higher number of sites that required additional surgical and/or antibiotic treatment. Therefore, patients should be informed, from the beginning, of the value of the SPT in enhancing long‐term outcomes of implant therapy, particularly those affected by periodontitis.